2018
DOI: 10.1016/j.beem.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Central precocious puberty: From genetics to treatment

Abstract: Central precocious puberty (CPP) results from early activation of the hypothalamic - pituitary -gonadal (HPG) axis and follows the same sequence as normal puberty. While many factors involved in pubertal initiation remain poorly understood, the kisspeptin system is known to play a key role. Currently, mutations in the kisspeptin system, MKRN3, and DLK1 have been identified in sporadic and familial cases of CPP. The diagnosis is based on physical exam findings indicating advancing puberty and on laboratory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 70 publications
0
93
0
2
Order By: Relevance
“…However, basal LH of 0.3 IU/L has been proposed and widely adopted as the cut-off for diagnosing CPP in previous studies. 1,6,18,19 Basal LH levels of 0.3 IU/L or greater were also associated with peak LH levels of 8 IU/L or greater and were observed in normal girls with Tanner stages IV and V breasts. 6,18 Therefore, diagnostic accuracy of these 2 basal LH cut-offs was compared.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, basal LH of 0.3 IU/L has been proposed and widely adopted as the cut-off for diagnosing CPP in previous studies. 1,6,18,19 Basal LH levels of 0.3 IU/L or greater were also associated with peak LH levels of 8 IU/L or greater and were observed in normal girls with Tanner stages IV and V breasts. 6,18 Therefore, diagnostic accuracy of these 2 basal LH cut-offs was compared.…”
Section: Discussionmentioning
confidence: 92%
“…Our study demonstrated that basal LH level of 0.2 IU/L represented 95th percentile of PT girls with Tanner stage II breasts. However, basal LH of 0.3 IU/L has been proposed and widely adopted as the cut‐off for diagnosing CPP in previous studies . Basal LH levels of 0.3 IU/L or greater were also associated with peak LH levels of 8 IU/L or greater and were observed in normal girls with Tanner stages IV and V breasts .…”
Section: Discussionmentioning
confidence: 99%
“…Both adrenarche and gonadarche are involved in the development of pubic hair . During gonadarche (Figure ), the hypothalamic‐pituitary‐gonadal (HPG) axis is activated, and several hormones have been identified to participate in the activation of the HPG axis including kisspeptin, neurokinin B, dynorphin, leptin, and ghrelin . Kisspeptin, neurokinin B, and dynorphin are released by specialized neurons, the KNDy neurons in the hypothalamus .…”
Section: Physiological Processes In the Initiation Of Pubertymentioning
confidence: 99%
“…CPP is also caused by the early activation of the HPG axis, which results in the early development of uterus, ovary and early appearance of the corpus luteum. This process eventually causes the occurrence of CPP [2,11]. CPP seriously affects the physical development and mental health of children, but also increases the risk of metabolic diseases related to CPP [12].…”
Section: Discussionmentioning
confidence: 99%
“…Central precocious puberty (CPP) is caused by premature activation of the hypothalamic-pituitary-gonad (HPG) axis, which ultimately leads to the premature development of secondary sexual characteristics in children [1][2][3]. According to report, 1 out of every 5000 to 10,000 children develops CPP, and in general, the incidence of CPP in girls is much higher than that in boys [4].…”
Section: Introductionmentioning
confidence: 99%